The World of the Past. Vol. 1 - Hawkes, Jacquetta (1964)
Excavation reports in the words of the original discoverers: L. Woolley on the royal tombs at Ur; S. Lloyd on the history of excavations in Mesopotamia and on Sumerian sculpture; H. V. Hilprecht on Nippur.